Health Risk Assessment for Population via Consumption of Vegetables Grown in Soils Artificially Contaminated with Arsenic - , M. I. J. Aysha, H. M. Zakir, R. Haque, Q. F. Quadir, Tasrina R. Choudhury, S. B. Quraishi, M. Z. I. Mollah (Archives of Current Research International, 2017)
Aims: A pot experiment was conducted to assess potential health risk for adult male and female human through consumption of spinach and tomato grown in soils artificially contaminated with arsenic (As). Study Design: The experiment was laid out followed by completely randomized design (CRD) with four replications. Place and Duration of Study: Net house of the Department of Agricultural Chemistry, Bangladesh Agricultural University, Mymensingh-2202 during the period from October 2015 to March 2016. Methodology: There were two types of soils (farm and industrial contaminated) and three treatment combinations viz. 0, 15 and 30 mg Kg-1 As for the test crops. Both spinach and tomato fruits were harvested at maturity. The amounts of As present in the dried edible and non-edible parts of the vegetables were extracted using di-acid mixture and concentrations in aqueous extracts were measured by hydride generation atomic absorption spectrophotometer (HG-AAS). To measure health risk, target hazard quotients (THQ) was calculated using the general formula established by the US EPA. Results: Among the growth parameters length of shoot, fresh and dry weight of spinach leaves and number of leaves per plant for both spinach and tomato were comparatively higher in different treatments of contaminated soils. But average length, fresh and dry weight of roots were higher for spinach grown in farm soil. The gross yield of spinach ranged from 42.9-48.9 and 101.1-132.6 g pot-1 in farm and contaminated soils, respectively. The accumulation patterns of As in different parts of spinach and tomato plants were in the order- root > leaf and root > leaf > shoot > fruit, respectively. Daily As intake from spinach was almost same for both soils at treatment As-15 but it was higher for farm soil at treatment As-30. But daily As intake from tomato fruits was higher for industrial contaminated soil. Target hazard quotient (THQ) values for As was almost same due to consumption of spinach for both soils at treatment As-15 but it increased proportionally at treatment As-30 in farm soil. On the other hand, THQ values were higher for consumption of tomatoes grown in industrial contaminated soils. Conclusion: The study results inferred that 15 mg Kg-1 available As in soil is enough to create health risk for population and leafy vegetables i.e. spinach is more harmful than fruit vegetables i.e. tomato. Furthermore, industrial contaminated sites are more susceptible than agricultural farm sites, and regarding health risk female are more vulnerable than male.